Socio-economic Context of Migration - Asuah, Zakari Akurigo (Univerzita Pardubice, 2022)
The study's goal is to identify and assess major migration movements and their impact on the socio-economic development of the Czech Republic Regions. The thesis explored descriptive analysis to examine the theoretical arguments for identifying major determinants of migration in Central and Eastern European Countries. The study also investigates the migration trend in the Czech Republic and the socioeconomic effects of migration on the Czech Republic. Whiles correlation analysis was used to analyse the effect of migration on the Size and population of the Czech Republic, content analysis was conducted identify major determinants of migrations in Czech Republic. Emphasis was based on selective aspects of migration attitude. Issues associated with accommodation, ad-culturation, assimilation and integration are dealt with. The findings of the study, which were based on data collected and qualitatively analysed, revealed that the country derived socio-economic benefits from the labour activities of migrants from both the EU-28 and non-EU countries. Immigration had a significant effect on the size of the population of the Czech Republic whereas emigration was insignificant. Furthermore, the Czech Republic's access to EU membership facilitates the increasing number of immigrants into the country. Immigrants close up the labour deficiency gap in the country. In addition, the analysis show regions which have high immigrants are more developed than regions with a low immigrant turnout. The thesis's findings show that immigrants contribute to the formation and development of regions in the Czech Republic. Migration, therefore, has a positve impact on the socio-economic development of regions in Czech Republic.
Keywords: WordsMigration; international migration; immigration; regional economic formation aspects of migration; foreign immigrant; migration determinants; Migration Impacts on the Czech Republic's Economy; Impact on Labor Market; migrace; mezinárodní migrace; imigrace; zahraniční imigrant; determinanty migrace; Česká republika; ekonomika; trh práce